IgG antibody response against Anopheles salivary gland proteins in asymptomatic Plasmodium infections in Narino, Colombia (2020)
ABSTRACT: Background: The humoral immune response against Anopheles salivary glands proteins in the vertebrate host can reflect the intensity of exposure to Anopheles bites and the risk of Plasmodium infection. In Colombia, the identification of exposure biomarkers is necessary due to the several Anopheles species circulating. The purpose of this study was to evaluate risk of malaria infection by measuring antibody responses against salivary glands extracts from Anopheles (Nyssorhynchus) albimanus and Anopheles (Nys.) darlingi and also against the gSG6-P1 peptide of Anopheles gambiae in people residing in a malaria endemic area in the Colombian Pacific coast. Methods: Dried blood spots samples were eluted to measure the IgG antibodies against salivary gland extracts of An. albimanus strains STECLA (STE) and Cartagena (CTG) and An. darlingi and the gSG6-P1 peptide by ELISA in uninfected people and microscopic and submicroscopic Plasmodium carriers from the Colombia Pacific Coast. A multiple linear mixed regression model, Spearman correlation, and Mann-Whitney U-test were used to analyse IgG data. Results: Significant differences in specific IgG levels were detected between infected and uninfected groups for salivary glands extracts from An. albimanus and for gSG6-P1, also IgG response to CTG and gSG6-P1 peptide were positively associated with the IgG response to Plasmodium falciparum in the mixed model. Conclusion: The CTG and STE An. albimanus salivary glands extracts are a potential source of new Anopheles salivary biomarkers to identify exposure to the main malaria vector and to calculate risk of disease in the Colombian Pacific coast. Also, the gSG6-P1 peptide has the potential to quantify human exposure to the subgenus Anopheles vectors in the same area. Keywords: An. (Nys.) albimanus; An. (Nys.) darlingi; Antibodies; Asymptomatic malaria; Bite exposure.